Konservasi Penggunaan Energi Listrik di Pabrik Area Proses Minyak (Studi Kasus PT. Indofood CBP Sukses Makmur Palembang) - Yansuri, Daeny Septi; Subanto, Subianto; Aidil Fitra, M. Wahyu (Jurnal Ampere, 2023)
PT. Indofood CBP Sukses Makmur Palembang is one of the large companies in the city of Palembang which operates in the food industry, one of which is the production of instant noodles. This company requires quite a bit of electrical energy so that the factories can continue to produce the desired number of products. The aim of this research is to find out about the use of electrical energy in the oil processing factory area of PT. Indofood CBP Sukses Makmur Palembang, to find out how much electrical energy hasbeen used in the PT oil processing factory area. Indofood CBP Sukses Makmur Palembang, how is electrical energy used in the oil processing factory area of PT. Indofood CBP Successfully Prosperous Palembang. This research uses observation, literature and interview methods. The results of this research are that the efficiency of electrical energy use in the factory is 70.23%, the use of electrical energy in the oil processing area factory of PT. Indofood CBP Sukses Makmur Palembang is still quite adequate, thereare still potential opportunities for saving electrical energy, namely 3,270.53 kWh, or in percentage terms it is 29.77%.